Does Emotional Intelligence Dwindle the Stress Due to Time Pressure and Work Overload? A Case Study of Nurses in Public Hospitals - Rafiq, Dr. Imran; Azhar, Dr Sarah; Mordhah, Dr. Najwa; Hussain, Dr. Jawad; Parveen, Dr Asma (The journal of contemporary issues in business and government, 2022)
The objective behind this research paper was to observe the impact of emotional intelligence on stress which is triggered by time pressure and due to work overload. With no regard to public or private organization setup, time pressure and work overload are reported by employees in general. Nurses are face the issue on daily basis. Stressful conditions due to time pressure and workload often lead to many organizational concerns in terms of mental health, physical health, absentees‟ turnover, emotional burnout etc. emotional intelligence is considered a best-coping strategy and it is studied with many organizational variables which positively related to positive variable and inversely related negative variable. Time pressure and workload werestudied with emotional intelligence it was observed that emotional intelligence was inversely related to time pressure and work overload. For this purpose, SmartPLS 3.0 was used to find the path coefficients and R-square, the output shows that the path coefficient for work overload (-0.55) and for time pressure (-0.38), the R-square (0.31) and (0.14) for work overload and time pressure with significance P-value (0.000) (0.000) and T-statistic value (14.9) (8.5) respectively. Nurses of the three main hospitals of Peshawar was the observing unit. And data was collected through self- administrated questionnaires, a stratified and systematic random sample was used to obtain the sample size of 359 out of approximately 2000 nurses including the adjusting nursing schools which works under these hospitals setting.